Tramadol and Tapentadol Induce Conditioned Place Preference with a Differential Impact on Rewarding Memory and Incubation of Craving - Barbosa, Joana (2023)
Tramadol and tapentadol, synthetic opioids commonly prescribed for moderate-to-severe pain, have a unique pharmacology that optimizes their analgesia and safety. However, they are not devoid of risks, presenting addictive, abuse, and dependence potential. While tramadol-reinforcing properties have been documented by various studies with human and animal models, including conditioned place preference (CPP) assays, no similar studies have been performed with tapentadol. In the present study, we performed CPP assays by intraperitoneally administering Wistar rats with a tramadol/tapentadol therapeutic dose. Animal permanence and the number of entries in the CPP compartments were recorded in the preconditioning phase and then 1 (T1), 7 (T7), and 14 (T14) days after conditioning. Both opioids induced a change in place preference (T1), suggesting that they have short-term reinforcing properties. However, only tramadol was associated with place preference retention (T7 and T14), with an increase in the number of entries in the opioid-paired compartment (T1 and T7), showing that it causes rewarding memory and incubation of craving. The results indicate that at therapeutic doses: (1) both drugs cause short-term rewarding effects and (2) as opposed to tramadol, tapentadol does not cause CPP retention, despite its higher central nervous system activity and stricter scheduling.